2010
DOI: 10.1111/j.1541-4337.2010.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Total Protein Methods and Their Potential Utility to Reduce the Risk of Food Protein Adulteration

Abstract: Kjeldahl and combustion (Dumas) methods are widely accepted for total protein determination but lack analytical selectivity for protein because they measure protein on the basis of sample nitrogen content. Adulteration incidents exploiting this analytical vulnerability (for example, melamine) demonstrate that these methods are no longer sufficient to protect the public health. This article explores the challenges and opportunities to move beyond total nitrogen based methods for total protein measurement. First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(137 citation statements)
references
References 191 publications
(381 reference statements)
1
130
0
5
Order By: Relevance
“…Broken grain QTL in these regions has also been mapped in cultivated germplasm (Septiningsih et al, 2003). The main advantages of the Kjeldahl method for food protein analysis are its high level of precision, its compatibility with nearly all food matrices, its wide recognition in the food analytical and regulatory communities, and its options for automation (Moore et al, 2010). Protein, an important factor affecting the eating quality of rice, was considerably high (>7%) for all variants (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Broken grain QTL in these regions has also been mapped in cultivated germplasm (Septiningsih et al, 2003). The main advantages of the Kjeldahl method for food protein analysis are its high level of precision, its compatibility with nearly all food matrices, its wide recognition in the food analytical and regulatory communities, and its options for automation (Moore et al, 2010). Protein, an important factor affecting the eating quality of rice, was considerably high (>7%) for all variants (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Moisture was determined by gravimetrically using moisture analyzer (OHAUS MB45, USA) at 105°C, ash amount was performed according to AOAC [25] method using burning in a furnace (Nuve MF 110, Turkey) at 650±25°C. Total protein was determined by nitrogen determination according to Dumas method (combustion) using nitrogen analyzer (NDA 701, Italy) [26,27]. Total oil was performed according to AOAC [28] method using Soxhlet extraction systems (Gerhart Soxtherm Multistat, UK).…”
Section: Methodsmentioning
confidence: 99%
“…From the result, it was revealed that BHFs could be potential keratinous bio-resource based on their notable CPC%. According to Moore et al, the proximate composition may not give the exact protein content in a fiber [52]. However, the presence of elements such as C, N, O and S (key elements in amino acids) in significant amounts in the BHFs indicates that, with appropriate methods of extraction, substantial amount of useful keratins can be tapped from these fibers.…”
Section: Proximate Compositionmentioning
confidence: 99%